2013
DOI: 10.1017/s0007114513002079
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between anthropometric indicators and cognitive performance in Southeast Asian school-aged children

Abstract: Nutrition is an important factor in mental development and, as a consequence, in cognitive performance. Malnutrition is reflected in children's weight, height and BMI curves. The present cross-sectional study aimed to evaluate the association between anthropometric indices and cognitive performance in 6746 school-aged children (aged 6 -12 years) of four Southeast Asian countries: Indonesia; Malaysia; Thailand; Vietnam. Cognitive performance (non-verbal intelligence quotient (IQ)) was measured using Raven's Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
56
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(74 citation statements)
references
References 29 publications
8
56
1
4
Order By: Relevance
“…However, the results of this study showed that there was no significant relationship between height-for-age (z-score) and IQ (p> 0.05). This study was in line with other studies [16], but it was different with some recent research saying there was a significant relationship between HAZ and IQ [7,[17][18][19][20]. Small brain size can be caused by a smaller body size so that the number of cells in the brain is reduced and not by the standard [8].…”
Section: Discussionsupporting
confidence: 86%
“…However, the results of this study showed that there was no significant relationship between height-for-age (z-score) and IQ (p> 0.05). This study was in line with other studies [16], but it was different with some recent research saying there was a significant relationship between HAZ and IQ [7,[17][18][19][20]. Small brain size can be caused by a smaller body size so that the number of cells in the brain is reduced and not by the standard [8].…”
Section: Discussionsupporting
confidence: 86%
“…One other study also reported no improvements in WAZ after 96 weeks on second‐line ART [19]. Many children therefore remained severely underweight in some settings, which has implications for future cognitive development and mortality [28,29]. More data are needed to understand why we did not observe gains in weight after switch to second‐line ART.…”
Section: Discussionmentioning
confidence: 84%
“…[17] Other study in 2013 showed that children aged 6-12 years with significant underweight and short stature had IQ lower than 89. [18] Other studies demonstrated short statured children had abnormal neuropsychology examination and impaired cognitive function, attention, memory process, visual perception, and verbal comprehension compared to normal children. [19] A study in South Africa assessing cognitive factors and stunting demonstrated that there was no significant correlation between stunting and child performance using Vineland Social Maturity Scale (VSMS), but closely and significantly related when using Revised-Denver Prescreening Developmental Questionnaire (R-DPDQ).…”
Section: Discussionmentioning
confidence: 97%